Strong reinforcement effects in 2D cellulose nanofibril–graphene oxide (CNF–GO) nanocomposites due to GO-induced CNF ordering. Issue 34 (13th August 2020) - Mianehrow, Hanieh; Lo Re, Giada; Carosio, Federico; Fina, Alberto; Larsson, Per Tomas; Chen, Pan; Berglund, Lars A.
Abstract : Nanocomposites from native cellulose with low 2D nanoplatelet content are of interest as sustainable materials combining functional and structural performance. Abstract : Nanocomposites from native cellulose with low 2D nanoplatelet content are of interest as sustainable materials combining functional and structural performance. Cellulose nanofibril–graphene oxide (CNF–GO) nanocomposite films are prepared by a physical mixing–drying method, with a focus on low GO content, the use of very large GO platelets (2–45 μm) and nanostructural characterization using synchrotron X-ray source for WAXS and SAXS. These nanocomposites can be used as transparent coatings, strong films or membranes, as gas barriers or in laminated form. CNF nanofibrils with random in-plane orientation, form a continuous non-porous matrix with GO platelets oriented in-plane. GO reinforcement mechanisms in CNF are investigated, and relationships between nanostructure and suspension rheology, mechanical properties, optical transmittance and oxygen barrier properties are investigated as a function of GO content. A much higher modulus reinforcement efficiency is observed than in previous polymer–GO studies. The absolute values for modulus and ultimate strength are as high as 17 GPa and 250 MPa at a GO content as small as 0.07 vol%. The remarkable reinforcement efficiency is due to improved organization of the CNF matrix; and this GO-induced mechanism is of general interest for nanostructural tailoring of CNF-2D nanoplatelet composites.